Decellularized matrix for repairing intervertebral disc degeneration: Fabrication methods, applications and animal models. (February 2023) - Qian, Hu; He, Li; Ye, Zhimin; Wei, Zairong; Ao, Jun
Abstract: Intervertebral disc degeneration (IDD)-induced low back pain significantly influences the quality of life, placing a burden on public health systems worldwide. Currently available therapeutic strategies, such as conservative or operative treatment, cannot effectively restore intervertebral disc (IVD) function. Decellularized matrix (DCM) is a tissue-engineered biomaterial fabricated using physical, chemical, and enzymatic technologies to eliminate cells and antigens. By contrast, the extracellular matrix (ECM), including collagen and glycosaminoglycans, which are well retained, have been extensively studied in IVD regeneration. DCM inherits the native architecture and specific-differentiation induction ability of IVD and has demonstrated effectiveness in IVD regeneration in vitro and in vivo. Moreover, significant improvements have been achieved in the preparation process, mechanistic insights, and application of DCM for IDD repair. Herein, we comprehensively summarize and provide an overview of the roles and applications of DCM for IDD repair based on the existing evidence to shed a novel light on the clinical treatment of IDD. Graphical abstract: Schematic illustrating role and application of decellularized matrix in repairing intervertebral disc degeneration. UC: Umbilical cord; AF: Annulus fibrosus; NP: Nucleus pulposus; IVD: Intervertebral disc; SIS: Small intestinal submucosa; DET: Detergent-enzymatic treatment. Image 1 Highlights: The fabricating procedures of DCM for IDD repair have progressed considerably. DCM materials could be applied as plain DCM, processed into hydrogel, and reactivated using bioactive substance. They show excellent in-vitro and in-vivo therapeutic efficiency for IDD repair. Ideal IDD animal models need to be developed to evaluate the efficiency of DCM.